Mucoadhesive Propolis Gel for Prevention of Radiation-Induced Oral Mucositis - R.A.S. Noronha, Vladimir; S. Araujo, Gustavo; T. Gomes, Rafael; H. Iwanaga, Samara; C. Barbosa, Maralice; N. Abdo, Evandro; Ferreira e Ferreira, Efigenia; C.C. Viana, Ana; A. Souza, Alexandre; R.L. Abreu, Sheila; R. Santos, Vagner (Current Clinical Pharmacology, 2014)
The objective of this phase II study was to determine the effectiveness of a mucoadhesive propolis gel in the prevention of radiation-induced oral mucositis. Twenty-four patients who were selected to undergo radiation therapy for oral cancer were included in this open-label trial. They were advised to use a mucoadhesive gel containing propolis 5,0% w/v three times a day starting one day before the course of radiation therapy and concluding after 2 weeks of radiation therapy. A weekly follow-up for evaluation of food intake, pain and grading of mucositis was performed. In order to confirm the absence of Candida-related mucositis in patients who developed mucositis, it was performed exfoliative cytology of buccal mucosa, palate and tongue and the material for Candifast® Candida species identification. At the end of the study was made the compliance of patients, quality, appreciation and acceptance of product evaluation. Twenty patients did not develop mucositis, two patients developed grade 1 mucositis and two patients developed grade 2 mucositis. None of the patients discontinued food intake and no pain was observed during the study. Candidosis was not detected in any patient. Mucoadhesive propolis gel could be considered as a potential topical medication for preventing radiation-induced oral mucositis. However, comparative phase III study with larger number of patients should be done for confirmation of the efficacy of the product.
Keywords: Head and neck cancer